Beten bei Jesus Sirach: Exegese, Theologie, Intertextualität und Hermeneutik der antiken Sprachversionen - Łopuch, Mirosław (Deuterocanonical and cognate literature studies, 2022)
The work sheds light on the theology of prayer in Jesus Sirach. In the exegesis of the seven selected passages, the connections with other biblical texts, their intentions, and the differences between the ancient language versions are also taken into account. This is in keeping with the character of the Book of Sirach, 68 percent of which has been handed down in Hebrew, then also in Greek and Syro-Aramaic